Bagan Edukatif Terhadap Meningkatkan Pengetahuan Ibu Tentang Rencana Terapi Pada Balita Diare dengan Dehidrasi - Potabuga, Isra Nur Utari Syachnara (Journal of Advanced Nursing and Health Sciences, 2022)
Background: Diarrhea is a symptom resulting from impaired function of digestion, absorption, and secretion. Diarrhea is caused by abnormal bowel and electrolyte transport. Worldwide, there are approximately 1.7 billion incidents of diarrhea each year. Approximately 24% of all deaths in children living in developing countries are related to diarrhea and dehydration. The incidence and morbidity of diarrhea is more prominent in low-income countries such as Asian and African regions and among children younger than 5 years. Purpose: The aim of this study was to determine the effect of health education using educative charts on mothers' knowledge about treatment plans for toddlers with diarrhea with dehydration at the toddler lotus posyandu. Methods: This type of research is a quantitative study with a Quasy Experiment with a Non-equivalent control group design with pre-test and post-test. Sampling technique with Purposive Sampling. The research subjects were mothers who had children under five at the toddler lotus posyandu. Results: The results showed a p value of 0.000 (p value <0.05), which means that there is an effect of using Instagram as an educational medium on the attitudes of pregnant women about monitoring danger signs of pregnancy in the new normal era. Conclusion: The conclusion of this study is that there is an effect of educational charts on mother's knowledge about treatment plans in toddlers with diarrhea with dehydration obtained from the post-test results between the experimental group and the control group with a significance value from the Mann-Whitney U Test, namely p = 0.00 or <0.05.